Antibiotics florfenicol and flumequine in the water column and sediments of Puyuhuapi Fjord, Chilean Patagonia. (July 2021) - Jara, Bibiana; Tucca, Felipe; Srain, Benjamín M.; Méjanelle, Laurence; Aranda, Mario; Fernández, Camila; Pantoja-Gutiérrez, Silvio
Abstract: Chile is a major global producer of farmed salmon in the fjords of Patagonia, and therefore a major consumer of antibiotics. We tested whether the antibiotics florfenicol and flumequine persisted in the large Puyuhuapi Fjord after the six months following mandatory concerted treatment by all salmon farms present in the fjord. Antibiotics were detected in 26% of analyzed samples, but only within the particulate phase, with concentrations of florfenicol of up to 23.1 ng L −1, where detected. Flumequine was present in one sample at trace concentration, and neither antibiotic was detected in the dissolved phase nor in surface sediments. A fugacity-based model predicted that flumequine should theoretically remain in surface sediments at the sub-Minimal Inhibiting Concentrations (sub-MIC) previously shown to promote selection for antibiotic resistance in bacteria. Our observations suggest that surface sediments might act as a reservoir for antibiotic resistomes of bacteria, and that bacteria bearing antibiotic resistance genes could eventually become a risk for human health through the consumption of marine products. Highlights: Antibiotics were detected in 26% of analyzed samples in Puyuhuapi Fjord. Maximum quantified concentration was 23 ng L −1 . A fugacity-based model predicted that flumequine remains in sediments at Sub-MIC.